Implementation of the Futsal Field Ordering Platform using the UCD Method - Agustia Hananto; Muhamad Mammun; Nurhayati (Information System; Universitas Buana Perjuangan Karawang, 2020)
The development of information technology is exploding. We cannot separate the need for information from the use and use of computers. With a computerized information system, the work done will be more effective and accurate. Karawang Futsal is a sports venue in the Karawang Regency. Using the futsal ordering system is still manual, the data input system which is still recording in the ledger, making reports is not accurate because of frequent miscalculations that result in making reports not on time because all processes are done. Therefore, with the existence of a computer system, all the needs for everything in the Karawang Regency Futsal will run.